CHALLENGES OF LOCAL WISDOM LEADERSHIP IN THE INDUSTRIAL REVOLUTION ERA 4.0 - I Gede Putu Kawiana (INFOKUM, 2022)
Era 4.0 is marked by significant developments in digital technology, changing the business, social and cultural landscape globally. In this context, local wisdom leadership becomes increasingly important in dealing with complex and rapid changes. The purpose of this research is to analyze the challenges faced by local wisdom leadership in dealing with the dynamics of Era 4.0. A qualitative approach is used to collect data through in-depth interviews with local leaders who have successfully integrated local values into their leadership. The results of this study reveal that local wisdom leadership in Indonesia comes from the excavation of the noble values of the Indonesian people which are contained in Pancasila values which include religious values, kinship, harmony, democracy and justice. This research also shows that local wisdom-based leadership in the Industrial Revolution 4.0 era faced challenges to values and culture due to technology and globalization. Leaders must strike a balance between traditional values and technological developments, while dealing with technological disruption, skills shortages and global competition. Complex communication challenges and value conflicts also arise. On the other hand, leaders need to maintain local cultural heritage in a sustainable development strategy that incorporates economic growth, social justice and environmental protection. In facing this challenge, leaders must adapt, integrate local values, and design a balanced and sustainable strategy.